Palm OS programming : the developer's guide - Rhodes, Neil, 1962- (O'Reilly, 2002)
With more than 16 million PDAs shipped to date, Palm has defined the market for handhelds, having dominated this class of computing devices ever since it began to outpace competitors six years ago. The company's strength is the Palm OS, and developers loyal to this powerful and versatile operating system have created more than 10,000 applications for it. Devices from Handspring, Sony, Symbol, HandEra, Kyocera, and Samsung now use Palm OS, and the number of registered Palm Developers has jumped to 130,000. If you know C or C++, and want to join those who are satisfying the demand for w.